The Influence of Mathematical Beliefs on The Mathematical Representation Ability of Students in Class VII - Najah, Khusnu (International Journal of Research in Mathematics Education, 2024)
Mathematical representation ability is the ability of students to express their mathematical ideas in the form of tables, diagrams, pictures, equations/words, and symbols. One of the things that is thought to affect students' mathematical representation skills is students' mathematical beliefs. Mathematical belief is an attitude or way a person welcomes mathematics based on the experience gained. This study aims to determine whether there is an effect of students' mathematical beliefs on the mathematical representation skills of seventh grade students at SMP Negeri 2 Sumbang, Banyumas Regency. The type of research used is quantitative with survey research method. The population in this study were seventh grade students of SMP Negeri 2 Sumbang which amounted to 216 students with a sample of 141 students. The variables of this study are mathematical beliefs as the independent variable and students' mathematical representation ability as the dependent variable. The data collection techniques used were questionnaires to measure students' mathematical beliefs and tests to measure students' mathematical representation skills. Data analysis used simple linear regression analysis. The results showed that there was an influence between students' mathematical beliefs on students' mathematical representation ability by 42.6%.